Respuesta Ferro-Piezoeléctrica de (K,Na,Li)(Nb,Ta,Sb)O3 Poroso - Barolin, Sebastián Andrés (2014)
KNL-NTS powder with (K0.44Na0.52Li 0.04)(Nb0.86Ta0.10Sb0.04)O 3 stoichiometry was prepared following the conventional ceramic method of mixing carbonates and oxides. KNL-NTS powder synthesis is carried out in solid state at 700°C for 3h. To obtain ceramic samples with different porosity the sintering of pellets is carried out in air at different temperatures between 1088 and 1125°C for 2h. Structural and microstructural characterizations are performed by XRD and SEM and the degree and type of porosity is determined by mercury intrusion porosimetry. The influence of sintering temperature on the porosity and its consequence on both the ferroelectric hysteresis loops and the piezoelectric response was evaluated. The maximum densification is achieved at 1125°C and the best ferroelectric response is achieved in sintered pellets at 1125°C. Meanwhile, it was observed that pellets sintered in a lower temperature range (1094-1100°C) where porosity reaches values up to 15 % have good ferroelectric piezoelectric response, similar to that found in the sintered pellets to 1125°C.